Effects of trihalomethanes on liver: a mouse model - Faustino-Rocha, A.I. (2015)
Introduction and objectives: Trihalomethanes (THMs) are disinfection byproducts found in chlorinated water. They are associated with cancer of various organs in human populations and experimental animal models. The aim of this study was to evaluate by histopathology the hepatic changes induced by THMs administered at low levels in a mouse model. Materials and methods: All procedures were made in accordance to the European Directive 2010/63/EU. Forty-two ICR male mice were randomly divided into 4 experimental groups: DBCM-exposed (n=11), BDCM-exposed (n=11), methanol-exposed (n=11) and a negative control (n=9). Animals from DBCM, BDCM and methanol-exposed groups received dibromochloromethane (DBCM), bromodichloromethane (BDCM) and methanol, respectively at a concentration of 117µg/Kg, once daily, by gavage, to a total of four administrations. Animals from control group only received water. Animals were sacrificed 4 weeks after DBCM, BDCM and methanol administrations. Blood biochemistry was performed for alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), total bilirubin (TB), albumin (Alb), total protein (TP), creatinine and urea. Hepatic samples were histopathological evaluated using hematoxylin and eosin (H&E), reticulin and Masson’s trichrome methods. Results: During the experimental protocol, 12 animals died and were excluded from the study. Animals exposed to THMs showed high levels of ALT and TB compared with methanol and control groups (p < 0.05). Histopathological analysis did not reveal any hepatic architectural changes. However, animals from the DBCM, BDCM and methanol groups exhibited multifocal inflammatory cell infiltrates, multifocal hepatocellular necrosis and cytoplasmic vacuolar degeneration, most frequently in the DBCM and BDCM-exposed groups. Hepatocellular nuclei exhibited a disperse chromatin pattern and prominent nucleoli in all animals from DBCM, BDCM and methanol-exposed groups. Reticulin and Masson’s trichrome methods showed normal collagen expression patterns in all groups, with no differences between exposed and control animals. Conclusions: The high levels of blood markers of hepatocellular damage (ALT and TB) and the histopathological findings indicate that both THMs, DBCM and BDCM when ingested at low doses exert toxic effects on hepatocytes.